A ZigBee-based wireless biomedical sensor network as a precursor to an in-suit system for monitoring astronaut state of health - Dong, Xiongjie (Kansas State University, 2014)
Networks of low-power, in-suit, wired and wireless health sensors offer the potential to track and predict the health of astronauts engaged in extra-vehicular and in-station activities in zero- or reduced- gravity environments. Fundamental research questions exist regarding (a) types and form factors of biomedical sensors best suited for these applications, (b) optimal ways to render wired/wireless on-body networks with the objective to draw little-to-no power, and (c) means to address the wireless transmission challenges offered by a spacesuit constructed from layers of aluminized mylar. This thesis addresses elements of these research questions through the implementation of a collection of ZigBee-based wireless health monitoring devices that can potentially be integrated into a spacesuit, thereby providing continuous information regarding astronaut fatigue and state of health. Wearable biomedical devices investigated for this effort include electrocardiographs, electromyographs, pulse oximeters, inductive plethysmographs, and accelerometers/gyrometers. These ZigBee-enabled sensors will form the nodes of an in-suit ZigBee Pro network that will be used to (1) establish throughput requirements for a functional in-suit network and (2) serve as a performance baseline for future devices that employ ultra-low-power field-programmable gate arrays and micro-transceivers. Sensor devices will upload data to a ZigBee network coordinator that has the form of a pluggable USB connector. Data are currently visualized using MATLAB and LabVIEW.
Keywords: ZigBee Wireless; NASA; Biomedical Sensing Network; Health Monitoring; Respiration Belt; ECG; Engineering (0537)